1999
DOI: 10.1159/000018284
|View full text |Cite
|
Sign up to set email alerts
|

Bullous and Pruritic Variant of Disseminated Superficial Actinic Porokeratosis: Successful Treatment with Grenz Rays

Abstract: We describe a case of intensively pruritic and partially bullous disseminated superficial actinic prorokeratosis, with acute flare-ups. Histopathological examination showed the characteristic cornoid lamella and subepidermal blister formation in one biopsy. Grenz ray treatment resulted in a marked regression of the skin lesions and pruritus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…DSAP lesions are reported to have the potential of transformation into squamous cell carcinoma, Bowen's disease, or basal cell carcinoma [2] and usually cause cosmetic disturbances, therefore treatment is indicated. Various pharmacological and physical treatment options exist, but to our knowledge there is only 1 case report of successful porokeratosis treatment with grenz rays [3] . We present 8 cases of DSAP, successfully treated with radiotherapy (RTx) at the University Hospital Zurich.…”
Section: Introductionmentioning
confidence: 99%
“…DSAP lesions are reported to have the potential of transformation into squamous cell carcinoma, Bowen's disease, or basal cell carcinoma [2] and usually cause cosmetic disturbances, therefore treatment is indicated. Various pharmacological and physical treatment options exist, but to our knowledge there is only 1 case report of successful porokeratosis treatment with grenz rays [3] . We present 8 cases of DSAP, successfully treated with radiotherapy (RTx) at the University Hospital Zurich.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this follicular variant, other clinical presentations of DSAP have also been described, such as bullous and pruritic variant 9 and a hyperkeratotic subtype 10 …”
mentioning
confidence: 96%
“…Our review of the published work disclosed that four additional cases of pruritic porokeratosis were reported later ( Table 1). [2][3][4][5] Of these, three exhibited clinical features similar to those described by Kanzaki et al Only the patient reported by 1tork and Kodetová 3 had no pre-existing lesions and no tendency for spontaneous resolution in the course of 16-month follow up; this patient manifested peripheral eosinophilia.…”
Section: Discussionmentioning
confidence: 70%